Certain Biological Aspects of Carangoides ferdau (Forsskal, 1775) and Scomberoides lysan (Forsskal, 1775) Caught from Drift Gillnets off Kanyakumari Coast - A., Balasubramanian; S.K., Chakraborty; K., Venkateshvaran; B., Meenakumari; M.R., Boopendranath; P., Pravin (Fishery Technology, 2025)
Carangid species of Carangoides ferdau and Scomberoides lysan caught using large mesh drift gillnets with mesh sizes of 135, 140, 145 and 150 mm from Kanyakumari coast of Tamil nadu, India were studied for two years from September 2002 to April 2004. Biological aspects such as fork length-weight, girth-weight, fork length-gill girth and fork length-maximum girth ratio of these two species were studied. In addition, condition factor and length at first maturity also were studied. Both the species exhibited negative allometric growth and ’b’ value of the length-weight and girth-weight relationship differed significantly (P<0.01). Estimated mean condition factors for C. ferdau were 1.826 and 4.021 based on length and maximum girth respectively. In the case of S. lysan mean condition factors estimated were 0.873 and 6.359 based on fork length and maximum girth respectively. Relationship of fork length-gill girth and fork length-maximum girth differed significantly from T. Coefficient of determination for length-girth relationships for both the species were high. C. ferdau and S. lysan attained length at first maturity at the fork length of 48.6 cm and 53.4 cm respectively.